Pengaruh Kemandirian Belajar Siswa Terhadap Hasil Belajar Matematika - Ratna Puspita Indah; Anisatul Farida (Pendidikan Matematika Universitas PGRI Yogyakarta, 2021)
The study aimed to identify the influence of independence for the mathematics student learning in SMP Al Irsyad Surakarta. The subject of this research are all students of class 8 SMP Al Irsyad Surakarta, which consisted of 120 students and the samples chosen with random sampling are 49 students in 3 class in the school year 2020/2021. Samples were taken using the Random sampling technique. The data of independence for the mathematics student learning using a questionnaire. This study using quasi experimental research. The prerequisite using the normality test and linearity test. The normality test by using Kolmogorov Smirnov and the linearity test by using Anova. When the a prerequisite fulfilled, so followed by the Linear Regression. The result showed there are significant impact study of independent learning. Independent learning have a positive influence of mathematics students, although the result is still below 50%. This may be affected by the lack of knowledge students learn about independence, so not been undertaken in full. The conclusions obtained that students could be more improve mathematics learning outcomes. Keywords: learning, independent learning, mathematics, learning outcomes